Mechanisms of autoimmune liver disease - Baier, Julia; Mattner, Jochen (Discovery medicine, 2014)
The immune system of the liver is characterized by a predominant innate component. Several innate immune cell populations have been implicated in the pathogenesis of immune-mediated hepatic diseases, which are frequently associated with systemic symptoms or with co-morbidities affecting other organ systems. Thus, next to tissue-specific factors, general tolerance mechanisms are affected in devastating hepatic disorders like primary sclerosing cholangitis (PSC), autoimmune hepatitis (AIH), or primary biliary cirrhosis (PBC). The innate immune cell populations abundantly detected within the liver and endowed with potent immunomodulatory capacities include innate lymphoid cells (ILCs) and natural killer T (NKT) cells. While both ILCs and NKT cells can be activated by different cytokines and/or chemokines, NKT cells also respond to (glyco-) lipid antigens engaging their canonical, semi-invariant TCR. Once activated, ILCs and NKT cells release copious amounts of Th1, Th2, and/or Th17 cytokines that shape subsequent innate and adaptive immune responses. Those immunomodulatory features as well as the recently described antigen-presenting capacity of ILCs and/or the bi-directional functional role of NKT cells might not only underlie the pathogenic mechanisms in the respective disorders, but also provide promising targets for clinical intervention. We will discuss these novel aspects as well as the role of alarmin-like cytokines such as IL-33 in the context of ILC and NKT cell activation and the consequences for the induction and progress of hepatic tissue damage and fibrosis.
EVALuna2:7662